Community counseling strategies to improve mental health literacy - Sindi Ayudia Pama; Diana Septi Purnama; Anisa Siti Nurjanah; Naufal Alwan Adilah; Muhammad Fahli Zatrahadi; Ellya Roza (Jurnal Konseling dan Pendidikan, 2023)
This study aimed to analyze community counseling strategies to increase public awareness about mental health services literacy. A cross-sectional survey design method was used and the samples included 339 respondents with an age range of 13 -50 years from various cities in Indonesia. The samples were selected using the Incidental sampling technique. Data were collected using a community awareness instrument for mental health services, implemented through an internet-based survey hosted on the Sobat Konseling account. The data analysis was conducted using descriptive statistics. The results showed that respondents genuinely cared about mental health after being exposed to various vital information. However, there was a lack of understanding regarding the symptoms of mental disorders. There was also limited awareness regarding the function of professional services, with only 1.47% of respondents selecting to consult a professional counselor, while others preferred to seek advice from friends and families, or refused to seek counseling at all. The results served as a reference for community counseling, providing insights into the formulation of strategies to enhance knowledge and skills in identifying mental disorders. Moreover, there is a need to build trust and understanding of the roles and experiences of counselors in handling psychological disorders through online counseling services.